Digest of State Practice 1 January–30 June 2018. (3rd July 2018) - Ruys, Tom; Vander Maelen, Carl; Van Severen, Sebastiaan
ABSTRACT: The Digest of State Practice covers events relevant to the Journal between 1 January 2018 and 30 June 2018.